Soil degradation in andean watersheds: a case study using remote sensing - Oñate-Valdivieso, Fernando; Oñate-Paladines, Arianna; Díaz, Ricardo (Frontiers in Earth Science, 2024)
Soil degradation is one of the greatest challenges faced by arid and semi-arid zones, as it causes a progressive loss of the capacity of soils to sustain life and human activities. In the present study, five spectral indices, individually associated with erosion, desertification, salinity, and soil sealing, were evaluated in a semi-arid region of the Ecuadorian Andes to study of soil degradation. The results were validated through field observations and samples processed in the laboratory. The spectral indices presented correlation coefficients between 0.5278 and 0.8809 with field observations. These indices provided useful information to understand the current state of the soils and their potential deterioration. The study area showed greater vulnerability to erosion caused by the combination of scarce vegetation, irregular topography, and significant seasonal rainfall. The advance of urbanization, mechanized agriculture, and overgrazing had a high impact by impermeabilizing considerable surfaces, while the advance of desertification and soil salinization showed little incidence in the study area. The systematic application of these indices would become a valuable means for monitoring soil degradation in Andean watersheds.